Biometric variables and productive attributes of wheat: mapping and correlation among variables - Pias, Osmar Henrique de Castro (2016)
The aim of this study was to evaluate the relationship between biometric variables quantified along the phenological development of the wheat crop with grain yield and production components. The study was carried out in an area of 4.7 ha. Initially the area was georeferenced and divided into a sampling grid of 50 x 50 m, resulting in 18 sample points. At each point three subplots of 2 x 1 m were marked. The emergency of plants seven days after emergence (DAE) (stage 1), number of plants, number of tillers, number of leaves per plant, root length, height, root dry mass, dry mass of the aerial part and number of nodes at 35 (stage 5), 57 (stage 8) and 80 (stage 10.3) DAE were evaluated. The yield component was determined regarding the number of spikes; 1000 grain weight; number of grains per spike and grain yield at 130 DAE (stage 11.4). Biometric differences in wheat plants from phenological stage 8 affect the productive components of crop. Wheat plants higher (height and number of nodes) and reduced root length showed higher productivity.